Understanding the Relationship Between Perceived Childhood Experiences and Relationship with God - Bahaa, Remaz (AUC Knowledge Fountain, 2024)
The present study explores the relationship between perceived childhood experiences and one’s current relationship with God in an Egyptian Muslim sample. While such relationship has been researched in Western contexts, there is a notable gap in understanding these dynamics within Muslim Middle Eastern cultures. In this study, 180 participants, brought up in Muslim households, were given the following questionnaires: both versions of the Parental Acceptance Rejection Questionnaire (PARQ) referring to the father and mother, Attachment to God Inventory (AGI), and Images of God (LAMBI Scale). The results presented the internal consistency of both the AGI and LAMBI scales with the Egyptian Muslim population in this study. In addition, the findings highlighted a significant positive correlation between perceived parental rejection (both maternal and paternal) and current anxious attachment to God. As for avoidant attachment with God, it was negatively correlated with viewing God as Benevolent but held no significant statistical power with perceived parental rejection. Furthermore, images of God held no statistically significant correlations with perceived parental rejection. In addition, self-rated religiosity was negatively correlated with maternal rejection. These findings contribute to a better understanding of the relationship between perceived childhood experiences and one’s relationship with God, providing insights into how cultural and religious factors might impact such relationship. These results hold implications for the counseling and developmental fields of psychology for Muslim populations, especially in further understanding the developmental pathway of one’s relationship with God.